The Development and Initial Validation of the Indonesian HIV Social Stigma (I-HSS) Scale - Wilandika, Angga; Sari, Diah Nur Indah (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Human immunodeficiency virus (HIV) social stigma causes people living with HIV (PLWH) to cover their HIV status. Also, HIV social stigma makes PLWH afraid of seeking information and treatment. Thus, to eliminate the HIV social stigma, measuring tools are needed to obtain the social stigma of the disease. The study aims are to develop and assessed the validation of the instrument of HIV social stigma in society. The instrument was developed through a multi-stage process of item generations and psychometric test of the instrument consists of content validity, construct validity and reliability test. The HIV social stigma scale was distributed to a cross-sectional sample of people in several regions in West Java, Indonesia (n=125). The final version of the I-HSS scales contained 25 items grouped into three dimensions (ignorance, prejudice, and discrimination) with a five-point Likert scale to score each item. Reliability was adequate for most dimensions (Cronbach’s alpha 0,76 - 0,78). Thus, the I-HSS scale were moderately correlated with one other (r = 0,52 - 0,84). Therefore, the I-HSS scale suggest a reliable and valid tool to measure social stigma toward people living with HIV in the community.